2021
DOI: 10.3390/educsci11110667
|View full text |Cite
|
Sign up to set email alerts
|

Students and Teachers Using Mentimeter: Technological Innovation to Face the Challenges of the COVID-19 Pandemic and Post-Pandemic in Higher Education

Abstract: The COVID-19 pandemic has prompted higher university lecturers to develop their digital skills in order to adapt to online teaching. A group of university teachers decided to evaluate the educational uses of Mentimeter to promote student participation and active learning. A questionnaire was answered by 400 students and 12 participating academics. These 12 academic respondents also participated in a focus group after experiencing this software during an academic course. Qualitative and quantitative data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 21 publications
0
33
0
11
Order By: Relevance
“…According to these authors, the COVID-19 situation and the restrictions in peer support affect mathematics students regardless of their gender or their previous skills. The need for a change in mathematics instruction given the current situation has been acknowledged by many researchers in the field [83][84][85] given the fact that peer support has now been highly limited.…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, the COVID-19 situation and the restrictions in peer support affect mathematics students regardless of their gender or their previous skills. The need for a change in mathematics instruction given the current situation has been acknowledged by many researchers in the field [83][84][85] given the fact that peer support has now been highly limited.…”
Section: Discussionmentioning
confidence: 99%
“…Pichardo et al [33] studied the strategy involved around student participation and the gaining of competencies. Using the digital high-education software Mentimeter, they noted that in synchronous and non-synchronous classes, Mentimeter promoted participation [33]. Furthermore, results from the study indicated that the software improved collaborative learning [33].…”
Section: Discussionmentioning
confidence: 99%
“…Using the digital high-education software Mentimeter, they noted that in synchronous and non-synchronous classes, Mentimeter promoted participation [33]. Furthermore, results from the study indicated that the software improved collaborative learning [33]. Bento et al [34] studied the adaptive process needed in response to the COVID-19 pandemic in a different scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Como recurso adicional, se percibe la necesidad de que los docentes integren el uso de calendarios digitales en sus recursos tecnológicos con el fin de administrar sus recursos didácticos en función de la planificación escolar. Al respecto, Pichardo et al (2021) indican que el uso de una herramienta de gestión de calendario digital garantiza la eliminación de reuniones superpuestas, errores en la gestión de recursos y confusiones de programación adicionales, lo que permite a los profesores y a los alumnos mantener una estructura coherente de las clases e incrementar la participación con base en la calidad de los materiales didácticos digitales.…”
Section: Discussionunclassified